Learners’ Perceptions of Online English Learning during COVID-19 Pandemic - Hafizah Rifiyanti (Scope : Journal of English Language Teaching, 2020)
The purpose of this study is to find learners’ perceptions of online English learning during the COVID-19 pandemic. The pandemic has made closure to schools and universities all over the world and online learning is a way of constraining the spread of COVID-19 virus. The study used a descriptive method by surveying 108 students from Management and Informatics programs of Institut Bisnis & Informatika Kosgoro 1957 (IBI K57). The data were collected through questionnaires by instruments consisting of learners’ perceptions about the effectiveness of learning English online, the accessibility of internet during English online learning, the technical performance of lecturers to teach English online, and the level of difficulty of language skills to learn online. The validity of the questionnaire was tested by using expert opinions. The results of the study indicated shifting face-to-face learning to online learning particularly for English classes is also an effective way during the pandemic, the accessibility of the internet in online learning, it is an important factor should exist during learning activities, the students assumed positively that most lecturers know how to teach English online learning by using online platforms used in IBI K57, and the learners perceived that listening section is the most difficult skill to learn in online English class. The study implied that online learning is an important alternative way to help teaching and learning in the situation of the pandemic, it considers using proper technology, quality, and instructors’ competence to enhance and to encourage learners engaged in online learning environment.